Evaluation method for reservoir damage of cementing slurry - Li, Ji; Wu, Dapeng; Zhang, Ran; Li, Chenguang; Zou, Qiang (Frontiers in Energy Research, 2023)
The damage of cement slurry to the reservoir is directly related to the production of oil and gas wells, and is a problem that must be solved for the efficient and economic development of oil and gas reservoirs. According to the characteristics and field conditions of reservoir damage caused by cement slurry, this paper analyzes the main factors affecting the degree of reservoir damage, puts forward the technical index requirements of the evaluation device, and establishes the evaluation method of reservoir damage caused by cement slurry in case of loss of injection. The results show that the influence of temperature on the damage of the cement slurry layer is small, and the influence of pressure difference on the damage to the cement slurry layer is large; When the pressure difference is 22 Mpa, the penetration damage rate caused by cement slurry to the pore center without mud cake attachment is about 43%. After a day of core maintenance, the permeability damage rate will reach 61.2%; The damage of cement slurry to the pore micro-fractured core is very serious. After 1 day of maintenance, the damage to the core permeability after cement slurry solidification is as high as 83%, with an average of 76.5%; When the risk of leakage is low, the cement slurry system with low density and low water loss can be used for cementing operation. The filtrate of cement slurry should be better matched with the formation clay minerals, formation water, and drilling fluid filtrate. When the risk of leakage is high, high-density cement slurry, balanced pressure cementing, pressure control cementing, and other technologies to avoid leakage can be used for cementing operations. When the cementing conditions are more difficult, the cementing slurry system can be used to dissolve the cementing slurry system at a later stage. The research results provide theoretical data support for the study of reducing the damage of cement slurry to the reservoir.